Spin-polarized transport through single-molecule magnet Mn6 complexes - SANVITO, STEFANO (My University, 2013)
The coherent transport properties of a device, constructed by sandwiching a Mn6 single-molecule magnet between two gold surfaces, are studied theoretically by using the non-equilibrium Green's function approach combined with density functional theory. Two spin states of such Mn6 complexes are explored, namely the ferromagnetically coupled configuration of the six MnIII cations, leading to the S = 12 ground state, and the low S = 4 spin state. For voltages up to 1 volt the S = 12 ground state shows a current one order of magnitude larger than that of the S = 4 state. Furthermore this is almost completely spin-polarized, since the Mn6 frontier molecular orbitals for S = 12 belong to the same spin manifold. As such the high-anisotropy Mn6 molecule appears as a promising candidate for implementing, at the single molecular level, both spin-switches and low-temperature spin-valves.
PUBLISHED
Keywords: Physics